Quantitative Morphologic Analysis of Cranial Vault in Twist1+/− Mice: Implications in Craniosynostosis. Issue 1 (21st December 2021) - Nuri, Takashi; Ota, Masato; Ueda, Koichi; Iseki, Sachiko
Abstract : Background: The haploinsufficiency in the TWIST1 gene encoding a basic helix-loop-helix transcription factor is a cause of one of the craniosynostosis syndromes, Saethre-Chotzen syndrome. Patients with craniosynostosis usually require operative release of affected sutures, which makes it difficult to observe the long-term consequence of suture fusion on craniofacial growth. Methods: In this study, we performed quantitative analysis of morphologic changes of the skull in Twist1 heterozygously–deleted mice ( Twist1 +/− ) with micro–computed tomographic images. Results: In Twist1 +/− mice, fusion of the coronal suture began before postnatal day 14 and progressed until postnatal day 56, during which morphologic changes occurred. The growth of the skull was not achieved by a constant increase in the measured distances in wild type mice; some distances in the top-basal axis were decreased during the observation period. In the Twist1 +/− mouse, growth in the top-basal axis was accelerated and that of the frontal cranium was reduced. In the unicoronal suture fusion mouse, the length of the zygomatic arch of affected side was shorter in the Twist1 +/− mouse. In one postnatal day 56 Twist1 +/− mouse with bilateral coronal suture fusion, asymmetric zygomatic arch length was identified. Conclusion: The authors'results suggest that measuring the length of the left and right zygomatic arches may be useful for early diagnosis of coronal suture fusion and for estimation of the timing of synostosis, and that more detailed study on the growth pattern of the normal and the synostosed skull could provide prediction of the risk of resynostosis. Clinical Relevance Statement: The data from this study can be useful to better understand the cranial growth pattern in patients with craniosynostosis.